Increasing cropping intensity and productivity through mungbean inclusion in wheat-fallow-T. Aman rice cropping pattern (Bangladesh Journal of Agricultural Research, 2018)
The experiment was conducted at the farmers’ field of Bhaluka Upazilla under On-Farm Research division, Bangladesh Agricultural Research Institute, Mymensingh during 2014-15 and 2015-16 to evaluate the performance of Wheat-Mungbean-T.aman rice improved cropping pattern against a farmers cropping pattern of Wheat-Fallow-T.aman rice. The findings of the study indicated that three crops could be grown successfully in sequence in the tested site. The higher rice equivalent yield (15.33 t hd-1 yr.-1), production efficiency (34.74 kg ha-1 day-1) and land utilization index (70.69 %) were obtained from the improved cropping pattern than the farmer’s one. Average gross return (Tk. 262750 ha-1), gross margin (Tk 126204 ha-1) and marginal benefit cost ratio (MBCR) 2.23 of the improved pattern indicate it’s superiority over farmers’ existing pattern. The fertility status of soil i.e. pH, organic matter, total N, available P, S, Zn and B content in soil were increased over the initial soil due to addition of mungbean biomass.Thus, inclusion of mungbean in the existing farmer’s cropping pattern will improve soil health and the system productivity as a whole.Bangladesh J. Agril. Res. 43(2): 333-343, June 2018